IMPLEMENTASI PENDIDIKAN KARAKTER GOTONG ROYONG MELALUI BUDAYA SEKOLAH DI SMP NEGERI 22 PONTIANAK - Supriadi, Muhammad; Achmadi, Achmadi; Atmaja, Thomy Sastra (Universitas Tanjungpura, 2024)
The purpose of this research is to see how the implementation of mutual cooperation character education is carried out through school culture at SMP Negeri 22 Pontianak. The method used is descriptive research with a qualitative form. Sources of data in the research conducted were school principals, curriculum representatives, Civics teachers and students. Data collection techniques were carried out through observation, interviews and documentation. Researchers used various stages to analyze the data, namely in the form of data collection, data reduction, as well as drawing conclusions and presenting data. The results of the field research obtained prove that the implementation of mutual cooperation character education through culture at SMP Negeri 22 Pontianak is carried out in routine, spontaneous, conditioning and exemplary activities. As for routine activities in the form of flag ceremonies, clean Friday, outdoor learning, class clean pickets, projects to strengthen Pancasila student profiles, August 17 competition activities and commemoration of the birthday of the Prophet Muhammad Saw and Isra' Mi'raj. Spontaneous activity, namely through fond of give infak and operation ants. Conditioning activities are obeying school rules, cleaning school hallways, tidying up chairs and desks in class and cleaning and tidying up the school library. Exemplary activities, namely through a commitment to dress at school and cleaning activities.